Blunting effect of hypoxia on the proliferation and differentiation of human primary and rat L6 myoblasts is not counteracted by Epo - Launay, T. (Cell Prolif, 2009)
Objectives:  The aim of this study was to evaluate whether hypoxia and/or erythropoietin would be able to modulate proliferation/differentiation processes of rat and human myoblasts. Materials and methods:  Rat L6 and primary human myoblasts were grown in 21% or 1% O(2) in the presence or absence of recombinant human erythropoietin (RhEpo). Presence of erythropoietin receptors (EpoR) was assayed using RT‐PCR and Western blotting techniques. Cell proliferation was evaluated by determining the doubling time and kinetics of cultures by counting cells. Cell differentiation was analysed by determining myogenic fusion index using antibodies against the myosin heavy chain. Expression of myogenin and myosin heavy chain (MHC) proteins were evaluated using the Western blotting technique. Results:  After 96 h culture in growth medium for 2.5 and 9 h, doubling time of L6 and human primary myoblasts respectively, had increased in 1% O(2) conditions (P < 0.01). Kinetics of culture showed alteration in proliferation at 72 h in L6 myoblast cultures and at 4 days in human primary myoblasts. The myogenic fusion index had reduced by 30% in L6 myoblasts and by 20% in human myoblasts (P < 0.01). Expression of myogenin and MHC had reduced by around 50%. Despite presence of EpoR mRNA and protein, RhEpo did not counteract the effects of hypoxia either in L6 cells or in human myoblasts. Conclusions:  The data show that exposure to hypoxic conditions (1% O(2)) of rat and human myoblasts altered their proliferation and differentiation processes. They also show that Epo is not an efficient growth factor to counteract this deleterious effect.